Association Between Homocysteine Levels and Risk of Depression in Office Workers With Vegan Diet in Jakarta - Karlina Lestari; Mudjihartini Ninik; Sutanto Krisadelfa (Green Publisher Indonesia, 2025)
Depression is a significant global public health concern, and the rising prevalence of vegan diets is currently linked to an increased risk of depression in adults. One contributing factor may be vitamin B12 deficiency in vegans, which can elevate homocysteine levels. This study aims to examine the relationship between homocysteine levels and depression risk among vegan office workers in Jakarta. The research employs a quantitative, cross-sectional design. The population consists of all vegan office workers in Jakarta, with a sample of 58 respondents selected through purposive sampling. Data collection involved interviews, anthropometric measurements, and laboratory tests. The data were analyzed using univariate and bivariate analyses via SPSS version 20. The findings revealed that the average plasma homocysteine level in participants was 3.48 μg/L, considered low. The average PHQ-9 score was 4.75, indicating no depression or moderate depression. Bivariate analysis showed no significant association between homocysteine levels and depression risk, with a p-value of 0.412, suggesting no correlation between homocysteine levels and depression risk in vegan office workers in Jakarta